Fabrication of carbon nanotube(CNT) - epoxy electrodes - Heng, Hui Zhi (2017)
Carbon nanotubes (CNTs) have been widely used as electrochemical sensor due to its excellent electrical, thermal, mechanical and chemical properties. It is generally accepted that the CNT tips have much better electrochemical properties than the sidewall of CNTs. In order to make use of CNT tips, CNT arrays were encapsulated in dielectric epoxy by degassing, and then the CNT tips were exposed by mechanical grinding and polishing. The aim of this final year project is to optimize the fabrication process to improve the performance of the CNT-based electrodes, in particular to reduce background current and increase electron transfer rate. Different parameters have been investigated. These include the mixing ratio of Epoxies, vacuum duration, vacuum pressure, Oxygen plasma duration, types of Epoxies used (Epolam 5015 and EpoFix), polishing processes and different curing processes. The CNT-Epoxy electrodes were then characterized by Cyclic Voltammetry using two different electrolytes. The results of background current and the peak potential difference, ∆Ep, were analysed and compared. The different background currents obtained and the current densities calculated have a co-relation with the area of exposed CNT tips during Cyclic Voltammetry, while the peak potential differences, ∆Ep, signify the electron mass transfer rate at the surfaces of the CNT-Epoxy electrodes during electrochemical reaction at the electrode.